Cook, les Instructions officielles de l’Amirauté et les recommandations de la Royal Society - Jean-Stéphane MASSIANI (E-REA)
For the three expeditions he led to the Pacific between 1768 and 1779, James Cook received a series of instructions from the Admiralty, which indicated the route he was to follow, the behaviour he was to observe with the indigenous populations he would meet and the various observations he was to write down in his journal. These secret instructions can to a great extent be considered as a travel guide Cook had to follow closely to satisfy the Lords of the Admiralty.Yet, the study of these various texts and of the recommendations the Royal Society formulated for the first voyage, leads to questions on their status and about their impact on the voyages themselves. To what extent did they influence Cook’s writing? Was he able to free himself from these directives and break away from the Admiralty injunctions to ultimately produce a self-governing text? These are the questions this article tries to answer.